2014
DOI: 10.5219/346
|View full text |Cite
|
Sign up to set email alerts
|

Goose`s eggshell strength at compressive loading

Abstract: The paper deals with the study of the goose eggs behaviour under compressive loading between two plates using testing device TIRATEST. The influences of the loading orientation as well as the effect of compressive velocity are studied. 226 eggs from Landes geese were chosen for the experiment. Eggs have been loaded between their poles and in the equator plane. Five different compressive velocities (0.0167, 0.167, 0.334, 1.67 and 5 mm.s-1) were used. The increase in rupture force with loading rate was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…This research extends our preliminary results obtained in [12]. In order to interpret the obtained results, some basic physical properties such as dimensional properties, description of the eggshell contour, sphericity, unit mass, egg surface, volume and eggshell thickness have been also evaluated.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…This research extends our preliminary results obtained in [12]. In order to interpret the obtained results, some basic physical properties such as dimensional properties, description of the eggshell contour, sphericity, unit mass, egg surface, volume and eggshell thickness have been also evaluated.…”
supporting
confidence: 72%
“…Because this is not typical for goose eggs this parameter has not been used in the given paper [12].…”
Section: Methodsmentioning
confidence: 99%
“…Comparatively, goose eggs present higher breaking strength (74.17-105.32 N); however, they are larger than turkey eggs, with average length of 78.26 mm and width of 53.62 mm (Zhang et al, 2017). Nedomova et al (2014) also reported higher breaking strength in goose eggs (63.80-101.92 N) loaded at the same compression speed of 0.33 mm s -1 as in the present study. On the other hand, much higher breaking strengths are obtained in large eggs, such as ostrich eggs 531.52-904.54 N (Nedomova et al, 2013), whereas small eggs, such as those of Japanese quails (weighing 10.58-14.25 g) have much lower breaking strength, of 6.2-11.4 N (Polat et al, 2007).…”
Section: Some Physical Morphological and Mechanical Characteristicssupporting
confidence: 53%
“…The average absorbed energy values determined in Zagorje turkey eggs (7.36-9.75 N mm) are higher than the values of 3.29-3.53 N mm observed in Lohmann chicken eggs (Altuntas & Sekeroglu, 2008), of 2.80-5.10 N mm in Hisex Brown chicken eggs (Nedomova et al, 2009) and of 3.41-7.88 N mm in Japanese quail eggs (Polat et al, 2007), but lower than the values of 8. .99 N mm reported for goose eggs (Nedomova et al, 2014) and much lower than those observed in ostrich eggs, of 90. 59-217.19 N (Nedomova et al, 2013).…”
Section: Some Physical Morphological and Mechanical Characteristicsmentioning
confidence: 67%
“…The results on the fracture strength of the whole eggshell show that this parameter is more or less dependent on the loading rate (Carter, 1979;Trnka et al, 2012;Nedomová et al, 2014). The same dependence may occur also for the eggshell membranes.…”
Section: Introductionmentioning
confidence: 73%